Improvement of Students’ Learning Outcomes by Using Crosswords Puzzle on Social Sciences Lesson - Frans Antonius Alaudin K. (STKIP Singkawang, 2019)
This research was conducted at SMP Negeri 11 Sungai Ambawang in IPS teacher who applied The Crossword Puzzle learning method to find out the improvement of students’ learning outcomes. This research is a School Action Research. The subject of this study was IPS or Social Studies teacher in grades VIII of SMP Negeri 11 Sungai Ambawang Kubu Raya Regency. This research took place in two cycles. Each cycle consisted of one meeting. The observation and documentation were used in data collection techniques. The type of data collected was observational data on students’ learning outcomes. The criteria for the success in this study was if the average percentage on students’ achievement indicators can reach 75% and has a minimum value of 70 according to KKM on SMP Negeri 11 Sungai Ambawang’s Curriculum. The application of the Crossword Puzzle method which was done by social studies teachers could improve students’ learning outcomes in grades VIII of SMP Negeri 11 Sungai Ambawang. This was evidenced by an increase in the average percentage of students’ learning outcomes for each cycle. This was evidenced by the percentage of students’ learning outcomes that reach the KKM’s value in the first cycle of 50% which was increased to 100% in the second cycle. It means that the number of students’ learning outcomes that reach the KKM’s value of 70 had exceeded the success criteria which was set at 75%.